Management of a delayed, post-traumatic rupture of splenic artery pseudoaneurysm in a patient with life threatening co-morbidities: A treatment challenge. (2020) - Kumari, Meena; Parwez, Masoom; Jain, Akash; Pandya, Bharati
Highlights: Even high-grade splenic injuries are manageable using interventional radiology with selective splenic artery embolization. Patient co-morbidities and other associated injuries affect the outcomes. Very morbid patients could be salvaged by judiciously executed ICU care and non-invasive procedure undertaken with informed risks. Abstract: Introduction: Splenic artery embolization (SAE) is an accepted intervention for patients with traumatic injury AAST III-IV in hemodynamically stable patients, splenic artery aneurysm and pseudoaneurysm (Brian and Charles, 2012). Unusual circumstances may pose different challenges in individual cases. Case presentation: A 52-year-old male on anticoagulants for past mitral valve replacement presented to us with history of blunt trauma sustained a month prior, was found to have grade IV splenic injury with delayed pseudo-aneurysmal rupture. In addition, his cardiac evaluation revealed an ejection fraction of 20%. A potential life threatening unstable cardiac status and hemodynamic irregularities accentuated due to the hemoperitoneum was an unusual challenge to deal with. After initial stabilization in ICU, the option of distal embolization of splenic artery was undertaken in a well-planned manner. Discussion: Unstable cardiac condition, anticoagulant therapy and delayed pseudo aneurysmal bleed led us into undertaking this procedure as a semi-emergency with calculated risks. We discuss this case due to the complexities and dilemmas on various aspects which we faced in his management. Conclusion: Patient tolerated the procedure well and was discharged on the third day of embolization. Our experience taught us the judicious implementation of a viable and only lifesaving option for an otherwise inoperable patient due to multiple co-morbidities and would strongly recommend this interventional radiological, relatively innocuous procedure for salvaging such patients.